1261 Agricultural machine-related injuries in south korea. (24th April 2018) - Kim, K; Choi, D; Lee, K; Chae, H; Lee, H; Choi, W
Abstract : Introduction: Along with a growth of machinery use and ageing population in Korean farms, risk of agricultural machine-related injury has been increasing. Agricultural machines have been reported as the main cause materials for agricultural injuries across many countries. The aim of this study is to examine risk and patterns of occupational machine-related injury among farmers in Korea. Methods: This study analysed data from the South Korea Farmers' Occupational Disease and Injury Survey that was conducted in 2015 by the Rural Development Administration, South Korea. Farm samples across all provinces were chosen by a multistage stratified method to represent the whole farms in South Korea. Survey was conducted through trained farm-visiting interviewers. The experience of occupational injury occurred in 2014 was surveyed, and the incidence rate of injury were calculated. Results: A total of 15 654 farmers over the age of 19 (9, 983 farm families) were surveyed. Agricultural machine-related injury accounted for 33.2% of all agricultural occupational injuries that need convalescence of one day and more due to the injury. The rate of occupational agricultural machine-related injury was 1.15 per 100 person-years among farmers who used agricultural machines. Injury rates were higher for males (1.18) than females, and consistently increased with age. The three top injury-leading agricultural machines were Gyeong-ungi, tractor, and bush cutter. Conclusion: Agricultural machines were the main cause of occupational injuries for Korean farmers. Priority for prevention efforts should be given to more vulnerable populations (i.e., older males). For effective prevention, comprehensive strategies that incorporate engineering safety and improvement of agricultural working environment (e.g., farm road) as well as safety training and education are needed. Funding: Rural Development Administration, Republic of Korea (Project No. PJ 01001705).